2018
DOI: 10.24071/joll.v18i2.1568
|View full text |Cite
|
Sign up to set email alerts
|

Written vs Spoken Narratives by Indonesian ESL Young Learners: A Case Study

Abstract: This study explores how Indonesian ESL Grade 2 elementary students studying in an international school in Jakarta produce written and spoken narratives. The stimulus material used to obtain the data was a four-panel comic strip with no written text. The findings revealed that both productions follow the basic global structure such as story elements, linearity of the storyline, and coherence. However, the written narratives contextually demonstrated formality while the spoken narratives displayed higher frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Also, in the analysis of the children's narrative production there were many hesitations/self-repairs and repetitions in the spoken modality when compared to the written modality. This finding is shared by several researchers [20]; [61]; [22]; [32] who conducted studies in narrative production. However, it should be noted that most repetitions in this study were due to the speech planning processes and the nature of the task.…”
Section: Differences In the Linguistic Discourse Structuresupporting
confidence: 53%
See 3 more Smart Citations
“…Also, in the analysis of the children's narrative production there were many hesitations/self-repairs and repetitions in the spoken modality when compared to the written modality. This finding is shared by several researchers [20]; [61]; [22]; [32] who conducted studies in narrative production. However, it should be noted that most repetitions in this study were due to the speech planning processes and the nature of the task.…”
Section: Differences In the Linguistic Discourse Structuresupporting
confidence: 53%
“…In a study conducted by [22] of Indonesian ESL Grade 2 elementary students' written and oral narratives it was found that both discourse productions had the crucial story components or structures. On the contrary, the written narratives were more formal whereas the spoken narratives used discourse structures such as contraction, hedges, repair, and repetitions.…”
Section: Discourse Structures Of Spoken and Written Languagementioning
confidence: 99%
See 2 more Smart Citations